Charakterisierung der mikrobiellen Lebensgemeinschaft eines sibirischen Permafrostbodens - Kobabe, Svenja (2005)
The soil characteristics and the bacterial community of the active layer (0-45 cm) of a permafrost affected tundra soil were analysed. The composition of the bacterial community was investigated by fluorescence in situ hybridisation (FISH) while BIOLOG Ecoplates were used to characterize microbial communities by determining the ability of the communities to oxidize various carbon sources. Arctic tundra soils contain large amounts of organic carbon, accumulated in thick soil layers and are known as a major sink of atmospheric CO2. These soils are totally frozen throughout the year and only a thin active layer is unfrozen and shows biological activity during the short summer. To improve the understanding of how the carbon fluxes in the active layer are controlled, detailed analysis of composition, functionality and interaction of soil microorganisms was done. The FISH analyses of the active layer showed large variations in absolute cell numbers and in the composition of the active microbial community between the different horizons, which is caused by the different environmental conditions (e.g. soil temperature, amount of organic matter, aeration) in this vertically structured ecosystem. Results obtained by universal protein stain 5-(4,6-dichlorotriazin-2-yl)aminofluorescein (DTAF) showed an exponential decrease of total cell counts from the top to the bottom of the active layer (2.3 × 109 to 1.2 × 108 cells per g dry soil). By using FISH, up to 59% of the DTAF-detected cells could be detected in the surface horizon, and up to 84% of these FISH-detected cells could be affiliated to a known phylogenetic group. With increasing depth the amount of FISH-detectable cells decreased as well as the diversity of ascertained phylogenetic groups. The turnover of substrates offered on the BIOLOG Ecoplates was slower and less complete in the deeper soil horizons. Especially in the upper 5 cm the turnover of some of the polymeric substances and some carbohydrates was much better than in deeper parts of the soil. The interaction ...